2012
DOI: 10.1142/s0218195912600047
|View full text |Cite
|
Sign up to set email alerts
|

Π/2-Angle YAO GRAPHS ARE SPANNERS

Abstract: We show that the Yao graph Y4 in the L2 metric is a spanner with stretch factor [Formula: see text]. Enroute to this, we also show that the Yao graph [Formula: see text] in the L∞ metric is a plane spanner with stretch factor 8.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…For k > 8, Bose et al [6] showed that Y k is a geometric spanner with spanning ratio at most 1/(cos θ − sin θ). This was later strengthened to show that for k > 6, Y k is a 1/(1 − 2 sin(θ/2))-spanner [5]. Damian and Raudonis [8] proved a spanning ratio of 17.64 for Y 6 , which was later improved by Barba et al to 5.8 [4].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For k > 8, Bose et al [6] showed that Y k is a geometric spanner with spanning ratio at most 1/(cos θ − sin θ). This was later strengthened to show that for k > 6, Y k is a 1/(1 − 2 sin(θ/2))-spanner [5]. Damian and Raudonis [8] proved a spanning ratio of 17.64 for Y 6 , which was later improved by Barba et al to 5.8 [4].…”
Section: Introductionmentioning
confidence: 94%
“…These graphs have been independently introduced by Flinchbaugh and Jones [11] and Yao [19], and are referred to as Yao graphs in the literature. It has been shown that Yao graphs are good approximations of the complete geometric graph [7,3,6,5,8,10,4].…”
Section: Introductionmentioning
confidence: 99%
“…Bose et al [13] have recently defined and studied the stretch factor of Yao ∞ 4 , a subgraph of the L ∞ -Delaunay triangulation on a set of points P in the plane. To describe this subgraph, we define a cone to be the region in the plane between two rays that emanate from the same point.…”
Section: Casementioning
confidence: 99%
“…They showed that Yao-graphs with at least 9 cones have spanning ratio at most 1/(cos θ − sin θ). This was later strengthened to show that Yao-graphs with at least 7 cones are 1/ (1 − 2 sin(θ/2))-spanners [13]. Recently, Damian and Raudonis [37] showed that the Y 6 -graph is a 17.64-spanner and Bose et al [14] showed that the Y 4 -graph has spanning ratio at most 663.…”
Section: Constrained Yao-graphsmentioning
confidence: 97%
“…This was later strengthened to show that Yao-graphs with at least 7 cones are 1/ (1 − 2 sin(θ/2))-spanners [13]. Recently, Damian and Raudonis [37] showed that the Y 6 -graph is a 17.64-spanner and Bose et al [14] showed that the Y 4 -graph has spanning ratio at most 663. Barba et al [4] showed that the Y 5 -graph is a 2 + √ 3 -spanner.…”
Section: Constrained Yao-graphsmentioning
confidence: 97%